Intellectual property rights and marine genetic resources in international law. Has the Agreement on the Conservation and Sustainable Use of Marine Biological Diversity in Areas Beyond National Jurisdiction? - Fernández-Tresguerres Sánchez, Ana Elvira (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
In June 2023, the text of the Agreement on the Conservation and Sustainable Use of Marine Biological Diversity in Areas Beyond National Jurisdiction (BBNJ) was finally adopted, concluding a decades-long process. One of the thorniest issues in its negotiation was the regime for marine genetic resources, and particularly, the associated intellectual property rights. Intellectual property rights, especially patents, on biological resources have often been a source of controversy. In the case of marine genetic resources, there are also considerations of North-South imbalances, the sovereignty of states over their resources, biopiracy and the protection of indigenous populations. Finally, the BBNJ agreement does not contain provisions on intellectual property rights associated with marine genetic resources. This issue has been taken over by the parallel process within the World Intellectual Property Organisation, which concluded in June 2024 with the adoption of a binding instrument on the subject. The new agreement, which is not yet in force, represents a giant step forward on a controversial and highly complex issue